ANALISIS NILAI PERUSAHAAN SEBELUM DAN SETELAH KONVERGENSI PSAK DENGAN IFRS - Reka Maiyarni (Universitas Trunojoyo Madura, 2014)
The purpose of this study was to obtain empirical evidence and understand the effects of capital structure, profitability, firm size, and managerial ownership on firm value before and after the convergence of GAAP with IFRS in manufacturing companies in the period 2008-2013. The selection of sample used purposive sampling and obtained 372 companies. The result of this study showed that prior to the convergence of GAAP with IFRS, the profitability affected the value of the company. After the convergence, profitability, firm size, and managerial ownership affected the value of the company. Meanwhile, the combined models indicatedthat profitability, firm size, and managerial ownership affected the value of the company. This study also showed that variable profitability, firm size, and managerial ownership affect the value of the companysimultaneously. The Chow test indicated that there were differences in the value of the company before and after the implementation of IFRS.